The Flow of African Spirituality into World Christianity - Nnamani, Amuluche-Greg (Mission studies, 2015)
Much of the spirituality peculiar to African Christians bears traces of the influence of African Traditional Religions (atr). Prayer traditions like incantations, melodious choruses and appeal to spirits, typical of atr, have infiltrated the religious life of African Christians both at home and in Diaspora, amongst Christians in the mainline churches as well as in the African Independent Churches. Though the flow of African spiritual heritage into Christianity happened in the early history of Christianity, it accelerated in the lives of slaves in diaspora in the West Indies, the Americas and Europe. Today, the process continues amongst African migrants fleeing the unbearable political and economic strangulations in Africa; they migrate with their culture and spirituality and impact on Christianity worldwide. It is the intent of this paper therefore to explore how the African mystic sentiment, frenzied excitement and spirit-laden spirituality, which combine the sacred and the secular in practical life, influenced Christian worship and thought down the ages and, in recent times, contributed to the emergence of the Pentecostal and charismatic spirituality.